Risk of major adverse events associated with gabapentinoid and opioid combination therapy: A systematic review and meta-analysis - Hahn, Jongsung; Jo, Youngkwon; Yoo, So Hee; Shin, Jaekyu; Yu, Yun Mi; Ah, Young-Mi (Frontiers in Pharmacology, 2022)
• Background: The use of opioid–gabapentinoid combinations has increased, raising several safety concerns. However, meta-analysis studies focusing on this issue are limited. • Objective: To evaluate the risk of central nervous system (CNS) depression, gastrointestinal (GI) adverse events, and mortality of combination therapy compared with those of opioid therapy and to explore the differences in the results according to study design and indications. • Methods: Relevant studies were selected (published before January 30, 2022) by searching the MEDLINE, Embase, and CENTRAL databases. The pooled odds ratios (OR) with 95% confidence intervals (CI) of the outcomes were estimated using the Mantel–Haenszel method. Subgroup and meta-regression analyses were performed according to study characteristics. Quality assessment was conducted using the Risk of Bias 2 tool for randomized controlled trials (RCTs) and Cochrane Collaboration’s Risk of Bias in non-RCTs tool for non-randomized trials. • Results: Adverse events were reported in 26 RCTs and 7 non-RCTs, and mortality was reported in 10 non-RCTs. Compared to opioid therapy, dizziness, cognitive dysfunction, and respiratory depression in combination therapy significantly increased in non-RCTs (OR 3.26, 95% CI 1.82–5.85; OR 3.13, 95% CI 1.51–6.50; OR 1.71, 95% CI 1.31–2.24, respectively), and a similar trend for dizziness and cognitive dysfunction was also identified in the RCT analysis, although the difference was not significant. Combination therapy for cancer pain was associated with the highest risk of sedation in subgroup analysis. Combination therapy significantly decreased the risk of GI adverse events, including nausea, vomiting, and constipation. The mortality risk associated with combination therapy was higher than that associated with opioid therapy (OR 2.76, 95% CI 1.26–6.05). • Conclusions: Opioid-gabapentinoid combination therapy could be associated with an increased risk of CNS depression and mortality, despite tolerable GI adverse events. These data suggest that combination therapy requires close monitoring of CNS depression, especially in cancer patients. Caution is needed in interpreting the clinical meanings owing to the lack of risk difference in respiratory depression in the RCT-only analysis and the absence of RCT or prospective studies investigating mortality.